Rare case of aberrant course of facial nerve traversing above oval window - Yash Heda, MD Radio-diagnosis; Sarfaraz Shaikh, MD, FRCR (Radiology Case Reports)
This research presents a unique observation of congenital conductive hearing loss linked to an atypical pathway of the facial nerve covering the oval window—a condition first reported by Henner. We explore the case of a 13-year-old boy suffering from lifelong bilateral hearing loss and tinnitus. Diagnostic imaging via high-resolution computed tomography of the temporal bone disclosed the unusual positioning of the facial nerves bilaterally, emphasizing the role of precise imaging in identifying uncommon anatomical deviations that impact clinical decisions.